The relationship between the compressive strength and ultrasonic pulse velocity concrete with fibers exposed to high temperatures - Hassiba, Belaribi; Mekki, Mellas; Farid, Rahmani (جامعة الوادي - university of el oued, 2018)
The paper analyses the effects of high temperatures on the concrete residual strength using ultrasonic velocity (UPV). An experimental investigation was conducted to study the relationship between UPV residual data and compressive strength of concrete with different mixture proportions, cubic specimens with water-cement ratio of 0.35. They were heated in an electric furnace at temperatures ranging from 200°C to 600°C. In this experiment a comparison was made between the four groups which include two types of fibers steel 0,19%, 0,25% and 0,5%, polypropylene: 0,05%, 0,11% 0,16 % by volume. Cube specimens were tested in order to determine ultrasonic velocity. The compressive strength was tested too. According to the results, relations were established between ultrasonic velocity in the specimens and the compressive strength at different temperature and the range of the velocity of the waves were also determined for this kind of concrete. Result of the test showed that UPV test can be successfully used in order to verify the consistency of structures damaged by fire
Article
Keywords: Ultrasounds; non-destructive testing; concrete, fibers, temperature, steel, polypropylene.